Early Modern Universities
1 online resource.
Keywords: "This book contains twenty essays by expert scholars of higher learning in the early modern period. Together they discuss topics that historians of universities have largely ignored: notably the extensive collaboration, and occasional conflicts, between university scholars, instructors, and administrators on the one hand, and students at academies, independent and dependent colleges, gymnasia, and Latin schools on the other. The contributions also cover a wide geographical range, covering universities, schools, academies, and the history of the book, in many European states, and Latin America"--